2-Methoxyestradiol inhibits bleomycin-induced systemic sclerosis through suppression of fibroblast activation. Issue 1 (January 2015) - Zhu, Lubing; Song, Yinghua; Li, Ming
Highlights 2-ME reduces skin and lung fibrosis and collagen protein and mRNA level in SSc mice. 2-ME inhibits SSc fibroblast proliferation in a dose- and time-dependent manner. 2-ME inhibits α-SMA expression of SSc fibroblasts. 2-ME decreases collagen production and increases its degradation in SSc fibroblasts. 2-ME is rising as a prospective agent for control of fibrosis in SSc.